Implementation of Religious Services Policy for the Elderly in South Sumatera: Analysis of Fiqh Siyāsah Tanfidziyah - Aprelia, Refita; Nurhayati, Agustina; Santoso, Rudi; Zaharah, Rita (Universitas Islam Negeri Raden Intan Lampung, 2023)
The implementation of social welfare and religious services for the elderly, in practice, involves various activities that must align with their religious beliefs. Ogan Komering Ulu Timur Regency in South Sumatra, as the implementing unit represented by the Department of Social Affairs, has the responsibility to identify the religious and spiritual needs of the elderly through planning, supervision, and the execution of religious and spiritual programs. This research aims to analyze the implementation of Article 6 of Government Regulation Number 43 of 2004 regarding the Implementation of Efforts to Improve the Social Welfare of the Elderly from the perspective of fiqh Siyāsah tanfidziyah in Ogan Komering Ulu Timur Regency, South Sumatra. The research method employed is field research, conducted by collecting data from the research location. The results indicate that the Department of Social Affairs has fulfilled its duty as the responsible government body by implementing various efforts to fulfill the spiritual needs of the elderly, although not entirely maximized due to several challenges. These challenges include the need for a deeper focus on individual religious preferences, the enhancement of religious program variations, and the search for solutions to overcome limited available resources. From the perspective of Siyāsah tanfidziyah, the government and stakeholders can ensure that religious and spiritual mental services for the elderly truly contribute to improved social welfare, as emphasized by the Quranic verse Q.S An-Nissa 58, underlining the importance of safeguarding trust and establishing fair laws.